Plasma Concentrations of Adiponectin in Patients with Coronary Artery Disease and Coronary Slow Flow - Muhammad Diah; Aznan Lelo; Dharma Lindarto; Zulfikri Mukhtar (Acta Medica Indonesiana, 2020)
Background: Adiponectin, an adipocyte-secreted hormone involved in energy homeostasis, has broad anti-inflammatory, antioxidant, and endothelium- and myocardial-protective effects, together with a potentially positive regulatory function in coronary microcirculation. Although the physiological role of adiponectin has not yet been fully elucidated, it may well be involved in the regulation of many of the inflammatory processes or lipid metabolisms that contribute to atherosclerosis. In this study we investigate the plasma concentration of adiponectin in patients with coronary artery disease (CAD), those with coronary slow flow (CSF) and in healthy subjects. Methods: this study was conducted according to a cross-sectional design involving 30 CAD, 30 CSF, and 30 healthy subjects. These subjects were sourced from the Dr. Zainoel Abidin Center Hospital, Banda Aceh, Indonesia, between December 2017 and February 2018. The plasma concentration of adiponectin was measured using enzyme-linked immunosorbent assay (ELISA) according to the manufacturer’s specifications. Results: there were statistically significant differences at p<0.001 between the CAD, CSF, and healthy-subject groups in terms of age, sex, systolic blood pressure, total cholesterol, triglycerides, and creatinine. Mean plasma concentrations of adiponectin in patients with CAD were significantly lower than in patients with CSF and in healthy subjects (CAD: 3.40 (0.87) μg/ml; CSF: 4.58 (2.32) μg/ml; healthy subjects: 5.65 (4.87) μg/ml; P<0.001). Conclusion: the findings suggest that low plasma adiponectin concentration is associated with atherosclerosis. Plasma concentrations of adiponectin may be related to the pathophysiology role of cardiovascular disease in both CAD and CSF patients.